The Relationship between Motivation and Family Support and Adherence to Taking Hypertension Medication in the Elderly - Trijayanti, Mardiyah; Parellangi, Parellangi; Amiruddin, Amiruddin (Rifa'Institute, 2024)
Introduction: Hypertension is a condition in which the increase in systolic blood is above the normal limit of more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. Objective: To determine the relationship between motivation and family support and adherence to taking hypertension medication in the elderly in Kampung Sekolaq Darat. Method: The design of this study is descriptive correlation with a cross-sectional approach. which will be held in February-May 2022. The population in this study is elderly people with hypertension in Sekolaq Darat village. The determination of the sample used Total Sampling, so a total of 35 respondents were obtained. The statistical test used is Chi-Square, if the t calculation (p-value) < 0.05 is obtained, then the Ha hypothesis is accepted and Ho is rejected. Result and Discussion: Motivation of the elderly in the moderate category (45.7%), then family support in the supportive category (65.7%) and adherence to taking hypertension medication in the elderly in the compliant category (54.3%). The relationship between motivation and adherence to taking hypertension medication in the elderly was obtained pValue = 0.00 and the relationship between family support and adherence to taking hypertension medication was obtained pValue = 0.00). Conclusion: There is a relationship between motivation and family support and adherence to taking hypertension medication in the elderly in Kampung Sekolaq Darat.